"Learning the Lingo": A Grounded Theory Study of Telephone Talk in Clinical Education. (July 2019) - Eppich, Walter J.; Dornan, Tim; Rethans, Jan-Joost; Teunissen, Pim W.
Abstract : Purpose: Workplace-learning literature has focused on doing, but clinical practice also involves talking . Clinicians talk not only with patients but also about patients with other health professionals, frequently by telephone. The authors examined how the underexplored activity of work-related telephone talk influences physicians' clinical education. Method: Using constructivist grounded theory methodology, the authors conducted 17 semistructured interviews with physicians-in-training from various specialties and training levels from two U.S. academic health centers between 2015 and 2017. They collected and analyzed data iteratively using constant comparison to identify themes and explore their relationships. They used theoretical sampling in later stages until sufficiency was achieved. Results: Residents and fellows reported speaking via telephone regularly to facilitate patient care and needing to tailor their talk to the goal(s) of the conversation and their conversation partners. Three common conversational situations highlighted the interplay of patient care context and conversation and created productive conversational tensions that influenced learning positively: experiencing and dealing with (1) power differentials, (2) pushback, and (3) uncertainty. Conclusions: Telephone talk contributes to postgraduate clinical education. Through telephone talk, physicians-in-training learn how to talk; they also learn through talk that is mediated by productive conversational tensions. These tensions motivate them to modify their behavior to minimize future tensions. When physicians-in-training improve how they talk, they become better advocates for their patients and more effective at promoting patient care. Preparing residents to deal with power differentials, pushback, and uncertainty in telephone talk could support their learning from this ubiquitous workplace activity. Abstract : Supplemental Digital Content is available in the text.